THE DEMAND FOR COLD CHAIN LOGISTICS OF AGRICULTURAL PRODUCTS IN VIETNAM - Phuong, Nguyen Hoang; Tuan, Nguyen Minh (International Journal of Psychosocial Rehabilitation, 2020)
Vietnam is one of the five leading countries in agricultural products and seafood exportation; however, the level of damage created by these products is considerably high due to the problems associated with its transportation and preservation, thereby generating product waste which has further implications on high domestic consumption as well as large reserves exportation. At the present, the cold supply chain model in Vietnam has been disseminated, but the majority of agricultural production and export enterprises have yet to fully apply this model at every stage of the distribution chain, from ‘farm gate to food plate’. Moreover, it would be difficult to meet some requirements in preserving products using logistics service, or instance, finding a reputable partner should be a challenging task. Hence, if the term “cold chain logistics” is widely known, the connection between farmers, enterprises, logistics companies for agricultural products could be strengthened, thus improving product quality.